Study the Effect of Antidiabetic Drugs on Bone Remodeling Biomarker and Bone Histological Structure in Wistar Rats Induced with Type 2 Diabetes - Shaimaa Adnan Abdalhussien Alshmmari, Suaad Mohammad Joda Al-Hadrawy (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes is usually associated with increase a risk of bone fracture. Many anti-diabetic drugs are used and the effects of these drugs on bone metabolism is one of the important issues that should be studied and not neglected. So, the goal of this study was to investigate the effect of two types of anti-diabetic drugs: Thiazolidinediones (TZDs) (30 mg/kg) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors (10 mg/kg) on bone minerals and Vit.D in laboratory female rats induced with type 2 diabetes mellitus. The study was conduct on animals house in Faculty of science/ Department of biology/University of kufa. And Central Laboratories/ In Medical City during the period from 27 october 2021 till the end of 22 February 2022.Thirty-two adults female Albino rats (Rattus norvigicus) were randomly divided to two main groups of sixteen animals, The first group was treated for a period of 2 weeks and the second group was treated for a period of 2 months. Each group of them was divided into secondary four groups of four rats including: a control (Co1 and Co2) were fed regular rats pellet, the second group (HFD 1 and HFD 2) were fed with high fat diet (42% lipid, 32%g sucrose, 14% protein), the third group were fed with high fat diet and treated with TZDs (30 mg/kg) and fourth group were fed with high fat diet and treated with SGLT-2i (10 mg/kg). The results of this study indicated that there was a significant increase (p≤0.05) on bone formation (PINP) and bone resorption biomarker (CTX-1) in the group induced with type 2 diabetes for the two treatment periods (two weeks and two months), and the increase was more significant (p≤0.05) in the group treated for two months compared to the treated group for two weeks. While the groups treated with TZDs and group treated with SGLT2i for two months showed a significant decrease (p≤0.05) in bone formation biomarker (PINP) compared with the other treated groups. In addition, the groups treated with TZDs for two months and group treated with SGLT2i for two weeks and two months showed a significant increase (p≤0.05) in bone resorption biomarker (CTX-1) compared with the other treated groups. The histological examination of the femur bone epiphysis in control1, HFD, HFD+TZDs, HFD+ SGLT-2i which treated for 2 weeks and control 2 which treated for 2 months revealed a normal bone structure. While, HFD groups treated four 2 months revealed that the bone matrix contained irregularly-oriented osteocytes within indistinct lacunae and multiple empty lacuna, increase adiposity of bone marrow and the presence of a resorption cavities in the irregular thin trabecular plates. In addition, groups treated with HFD+TZDs and HFD+ SGLT-2i four 2 months showed the presence of a resorption cavities, an empty lacuna, less dense appearance of bony tissue and osteocyte necrosis. Conclusion: Uncontrolled diabetes mellitus has adverse effects on bone metabolism, Long-term treatment with Thiazolidinedionse (TZDs) and SGLT-2 inhibitors, despite its control of blood sugar, has harmful effects on bone metabolism.